Treachery pigmentation pattern leads to misidentification: Tapinoma melanocephalum (Fabricius), Tapinoma pygmaeum (Dufour) and Tapinoma jandai sp. nov. (Hymenoptera, Formicidae) - Bernhard Seifert (Contributions to Entomology, 2025)
Discrete color morphs of ants, in the case reported here morphs with whitish versus blackish gaster pigmentation, may be misinterpreted as different species. This became clear in a morphometric study including 91 worker individuals of Tapinoma jandai sp. nov., Tapinoma melanocephalum (Fabricius, 1793) and Tapinoma pygmaeum (Dufour, 1857). The three species are clearly separable by a principal component analysis of 17 morphological characters under exclusion of pigmentation characters. This result is confirmed by a clear separation in a linear discriminant analysis with the classification of any specimen being confirmed with posterior probabilities of p > 0.9994. The study showed that just the holotype series of Tapinoma pithecorum Seifert, 2022 is a rare color variant of Tapinoma pygmaeum and consequently the former taxon is a junior synonym of the latter. In contrast, all remaining samples that formed the basis of the description of Tapinoma pithecorum are recognized as an undescribed species which is introduced here as Tapinoma jandai sp. nov. A consideration of 14 taxa of minute species showing similarities to the new species revealed that none of these is suspected of representing a senior synonym of T. jandai sp. nov. and that Tapinoma indicum Forel, 1895 should be transferred to the genus Ravavy Fisher, 2009. Based on examples in Formica, Camponotus, Cardiocondyla and the two cases reported here, it is argued that ant classification by simple color patterns is under increased risk of misclassification.